Glyphosate: risk or threat to human health and wild life - Pérez-Vázquez, Arturo; Fernández-Peña, María de Lourdes; Castañeda-Chávez, María del Refugio; Díaz-Rivera, Pablo (Revista Mexicana de Ciencias Agrícolas, 2024)
Glyphosate is the most used herbicide worldwide in agriculture over the past 20 years. Its use has led to side effects with direct damage to ecosystems, wildlife, and human health. Much of the world’s scientific community has joined the task of researching the effects of this herbicide and documenting sustainable alternatives to reduce its use. There are contradictions in the scientific literature in this regard, so it was proposed to carry out a meta-analysis of the scientific information in order to identify the effects derived from the use of glyphosate on human health and the environment. A systematic search of the Scopus database was conducted from 2014 to 2022. It was found that the main metabolite aminomethylphosphonic acid and the surfactant polyoxyethyl amine are present in the commercial formulation of Roundup® (glyphosate), are persistent and present toxicity in different tissues and organs of terrestrial and aquatic species, in addition to decreasing agricultural production by affecting the growth of seedlings. Other positions point out that glyphosate does not cause effects or exhibit toxicity. However, these claims lack credibility because of the type of compound used in toxicity bioassays. This review concludes that, for eminently precautionary purposes, it is necessary to reduce the use of this agrochemical in agriculture, the long-term effect of which puts human health and biota at risk. And, therefore, the need to generate regulations that control their use or restriction.
Keywords: environmental damage; glyphosate; herbicide